Buried pipe design - Moser, A. P. (Alma P.) (McGraw-Hill, 1990)
This text encompasses the design of underground pipe installations and the selction of correct equipment and materials, including soil parameters and all the essentials of both gravity-feed and pressure-feed piping systems.